New perspectives on human development - Budwig, Nancy; Turiel, Elliot; Zelazo, Philip David; Carlson, Stephanie M.; Wainryb, Cecilia; Nasir, Na'ilah Suad,eeditor; Nelson, Katherine (Cambridge, United Kingdom Cambridge University Press, 2017)
"New Perspectives on Human Development addresses fundamental questions of development with a unified approach. It encompasses theory and research on cognitive, social and moral, and language and communicative development, in various stages of life, and explores interdisciplinary perspectives. New Perspectives on Human Development revisits old questions and applies original empirical findings, offering new directions for future research in the field"--Provided by publisher.
Keywords: Developmental psychology; Developmental psychobiology